Penggunaan Primary Literature dengan Topik Psikotropika untuk Meningkatkan Pemahaman Hakikat Sains Siswa SMA (Universitas Negeri Semarang, 2022)
Indonesian education focuses more on content at the present time, while learning the true nature of science is not explicitly carried out, whereas the very learning of scienc is proving better if it’s explicitly done. Understnding the NOS is importent to scale up because it’s one of the components of the science literacy that is so necessary in the present era. This study aims to determine how an increased understanding of the nature of science and concept of students on psychotropic materials with learning analyzing the scientific articles about psychotropic. The topic of psychotropic is chosen because it's very contextual for adolescents, who are involved in the case of psychotropic abuse. This research uses the One Group Pre-test post-test design. The participants involved were 58 students of class XI MIPA from one high school in Bandung City. The instrument used in this study is instrument of NOS, concept and questionnaire of student responses. Instruments of understanding of the NOS and understanding the concept is given as pre-test and post-test. Based on the findings obtained at the pre-test, NOS understanding of students' is 22,09 with less category while the concepts understanding of the student get 10,61 scores with very lows categories. Based on the results of post-test, NOS understanding of students' obtained score 50,97 in a medium category and concept understanding of 40,79 in a medium category. NOS understanding of students' obtained a n-gain value of 0.37 which indicates an increase in the understanding with medium category. Understanding the concept of students obtained a n-gain value of 0.33 which also includes medium category. The findings obtained are also in accordance with the states positive and negative responses of the response questionnaire.